Financial Market Design and the Equity Premium: Electronic versus Floor Trading - JAIN, PANKAJ K. (Journal of Finance, 2005)
ABSTRACT We assemble the announcement and actual introduction dates of electronic trading by the leading exchanges of 120 countries to examine the impact of automation, controlling for risk factors and economic conditions. Dividend growth models and international CAPM suggest a significant decline in the equity premium, especially in emerging markets. Consistent with this reduction in the equity premium in the long run, there is a positive short‐term price reaction to the switch. Further analysis of trading turnover supports the notion that electronic trading enhances the liquidity and informativeness of stock markets, leading to a reduction in the cost of capital.